LL37:DNA complexes provide antimicrobial activity against intracellular bacteria in human macrophages. Issue 4 (18th July 2016) - Stephan, Alexander; Batinica, Marina; Steiger, Julia; Hartmann, Pia; Zaucke, Frank; Bloch, Wilhelm; Fabri, Mario
Abstract : Human macrophages internalize antimicrobial peptide (AMP):DNA complexes, which are ejected by neutrophils as part of neutrophil extracellular traps (NETs). A key finding of our study is that the AMP LL37 originating from LL37:DNA complexes targets mycobacterial membranes inside macrophages resulting in antimicrobial activity. Summary: As part of the innate host response neutrophils release neutrophil extracellular traps (NETs), protein:DNA complexes that contain a number of antimicrobial peptides (AMPs), such as cathelicidin. Human cathelicidin in its active form, LL37, has potent antimicrobial activity against bacteria. However, whether LL37 derived from NETs contributes to antimicrobial activity against intracellular pathogens remains unclear. Here, we report that NETs induced by mycobacteria contain cathelicidin. Human macrophages internalized NET‐bound cathelicidin, which is transported to lysosomal compartments. Furthermore, using a model of in vitro ‐generated LL37:DNA complexes we found that LL37 derived from such complexes attacks mycobacteria in macrophage phagolysosomes resulting in antimicrobial activity. Taken together, our results suggest a mechanism by which LL37 in complex with DNA contributes to host defence against intracellular bacteria in human macrophages.